2013
DOI: 10.1111/pce.12054
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci for freezing tolerance in a recombinant inbred line population of Arabidopsis thaliana accessions Tenela and C24 reveals REVEILLE1 as negative regulator of cold acclimation

Abstract: The ability to increase freezing tolerance when exposed to low temperatures is a property of many plant species from temperate climates and involves a wide array of metabolic adjustments and changes in gene expression. In Arabidopsis thaliana, natural accessions show high variation in their acclimation capacity, and freezing tolerance correlates with natural habitat temperatures. To investigate the genetic basis of this variation, a recombinant inbred line population from reciprocal crosses between the accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 56 publications
3
29
0
Order By: Relevance
“…This hypothesis is also supported by a report indicating that short-day-induced down-regulation of FT2 is involved in repressing vegetative growth and inducing bud set in poplar (see Pin and Nilsson 2012). We further propose that an ABA-dependent signaling mechanism for regulation of a putative homolog of the Arabidopsis circadian clock output gene RVE1-like is involved in regulating downstream genes containing cis-acting evening elements in a manner similar to that described in other systems (Meissner et al 2013;Franco-Zorrilla et al 2014). These pathways and markers may serve as new targets for manipulating vegetative production that reduce economic costs to land managers worldwide.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This hypothesis is also supported by a report indicating that short-day-induced down-regulation of FT2 is involved in repressing vegetative growth and inducing bud set in poplar (see Pin and Nilsson 2012). We further propose that an ABA-dependent signaling mechanism for regulation of a putative homolog of the Arabidopsis circadian clock output gene RVE1-like is involved in regulating downstream genes containing cis-acting evening elements in a manner similar to that described in other systems (Meissner et al 2013;Franco-Zorrilla et al 2014). These pathways and markers may serve as new targets for manipulating vegetative production that reduce economic costs to land managers worldwide.…”
Section: Discussionsupporting
confidence: 87%
“…If so, these results would be the first, to our knowledge, suggesting the potential for regulating this putative circadian clock output gene via crosstalk with an ABA-dependent pathway during osmotic stress. Additionally, the RVE1 transcription factor of Arabidopsis is known to bind to evening elements of target genes (Franco-Zorrilla et al 2014) and was also identified as a candidate gene for a QTL responsible for freezing tolerance in Arabidopsis, where it is considered a negative regulator of freezing tolerance (Meissner et al 2013). Interestingly, some DREB1/CBFs contain evening elements within their promoters, which is likely the binding site of CCA1 in other plant systems (Mizoi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These RNA-seq results were validated by analyzing the retention of several constitutively and alternatively spliced introns, whose adequate removal was specifically controlled by the LSM nuclear complex under low temperature or high salt conditions, in independent RNA samples from WT, lsm8-1 and lsm8-2 plants exposed 24 h to 4°C or 10 h to 150 mM NaCl through qPCR assays. Thus, we investigated introns belonging to genes described to regulate freezing tolerance, such as the transcriptional regulators MYB96, PRR5 and RVE1 or the cytokine receptor AHK3 (2730), or salt tolerance, including the interferon-related developmental regulator SAT32 , the Na + /H + antiporter NHX1 , the E3 ubiquitin ligase SIS or the protein kinase WNK8 (3134), in Arabidopsis. Figures 5C and D display that, in all cases, the retention patterns observed were as those deduced from RNA-seq experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, our results indicate that the LSM2–8 complex guarantees adequate levels of functional transcripts and, consequently, proteins of the corresponding genes. Among the introns whose correct splicing is ensured by LSM2–8 in response to low temperature, several belong to genes coding for proteins, such as PRR5, RVE1 or AHK3, that have been described to be negative regulators of freezing tolerance (2830). Under salt stress, LSM2–8 controls the accurate splicing of introns that are part of genes encoding proteins known to be positive regulators of Arabidopsis tolerance to high salt, including SAT32, NHX1 or SIS (3133).…”
Section: Discussionmentioning
confidence: 99%
“…Among three of the climate change stress agents (cold, heat, drought), three PUTs were found to be increased, two of which have homology to the REVEILLE gene, known for its involvement in circadian rhythm and as a negative regulator of cold tolerance [54]. The third up-regulated PUT is an ascorbate-specific transmembrane electron transporter, also referred to as cytochrome b561, which is critical to ascorbate recycling.…”
Section: Resultsmentioning
confidence: 99%